The Effect of The Preloading Method on Soil Consolidation Time at Binjai-Pangkalan Berandan Toll Road Sta 38+825 - Ramadhan, Fikri; Wulandari, Tika Ermita (Innovative: Journal Of Social Science Research, 2025)
Infrastructure development often faces challenges due to soft soil conditions, as encountered in the Binjai-Pangkalan Berandan Toll Road Construction Project at STA 38+825. Soft soil has low permeability, low bearing capacity, and a long consolidation period, making soil improvement necessary before construction. One commonly used method is preloading, which involves applying an initial load with temporary embankments to accelerate the soil consolidation process. This study aims to analyze the effect of the preloading method on the acceleration of soil consolidation time and the magnitude of soil settlement at the project site. The analysis was conducted using an analytical approach based on field soil test data, such as boring log data, Standard Penetration Test (SPT) data, and other soil parameters. The calculations were performed using Terzaghi’s One-Dimensional Consolidation Theory. The results show that the preloading method can accelerate the soil consolidation process to achieve 90% consolidation in 249 days. The total settlement observed during the preloading process was 65.246 cm. These findings indicate that the preloading method is effective in soft soil conditions to improve soil stability before the main construction phase begins.